2022
DOI: 10.1108/intr-04-2022-0238
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ignorance and bias on information security protection motivation: a case of e-waste handling

Abstract: PurposeProtection motivation theory (PMT) explains that the intention to cope with information security risks is based on informed threat and coping appraisals. However, people cannot always make appropriate assessments due to possible ignorance and cognitive biases. This study proposes a research model that introduces four antecedent factors from ignorance and bias perspectives into the PMT model and empirically tests this model with data from a survey of electronic waste (e-waste) handling.Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 114 publications
0
5
0
2
Order By: Relevance
“…Incorrect cyber risk perception leads to thinking that the individual has preventive measures, or the risk is low, not very serious and I will not be a target. Ament (2017) stated that optimism bias will lead to overconfidence on the skills of the individual as well as create a thinking that I will not be a target thus will not opt preventive measures due to that overconfidence and optimism bias [37] Cho et al, 2010 [38] and Chen & Yuan, 2022 [29]. Overconfidence and optimism bias will affect the decision making of the individual both in personal context as well as in organizational context [29] [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorrect cyber risk perception leads to thinking that the individual has preventive measures, or the risk is low, not very serious and I will not be a target. Ament (2017) stated that optimism bias will lead to overconfidence on the skills of the individual as well as create a thinking that I will not be a target thus will not opt preventive measures due to that overconfidence and optimism bias [37] Cho et al, 2010 [38] and Chen & Yuan, 2022 [29]. Overconfidence and optimism bias will affect the decision making of the individual both in personal context as well as in organizational context [29] [38].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the results of most of the individual studies of optimistic bias in the context of cyber security. Chen & Yuan, in a recent study found that due to optimistic bias, the decisions of the analysts will not be objective and will be biased and flawed [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Anonymity and Psychological Distance: The often anonymous nature of cyber threats can diminish the perceived immediacy and severity of these risks, affecting individual behavior in security practices [29]. 3) Cognitive Biases: Common cognitive biases, such as the illusion of invulnerability, can lead individuals to underestimate their likelihood of being targeted by cyberattacks [30]. 4) Adaptability to Changing Threats: The continual evolution of cyber threats necessitates that information security measures be flexible and responsive to new challenges [31].…”
Section: Unique Aspects Of Information Security Risk-takingmentioning
confidence: 99%
“…Further contributing to this field, AlGhamdi, Win, and Vlahu-Gjorgievska [37] and Solomon et al [38] provided models to assess and enhance compliance with information security controls and contextual security awareness, respectively, focusing on culturally and contextually sensitive frameworks [37,38]. Chen and Yuan [30] and [26] explored how ignorance, cognitive biases, and intelligence integration with personality traits influence security behaviors and compliance with preventive measures [26,30]. Our study extends these discussions using a quantitative modeling approach through Spearman correlation analysis and logistic regression.…”
Section: E Developments In Information Security Awareness Researchmentioning
confidence: 99%